2011
DOI: 10.1128/jvi.02694-10
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved YAGL Motif in Human Metapneumovirus Is Required for Higher-Order Cellular Assemblies of the Matrix Protein and for Virion Production

Abstract: YXXL motifs in cellular and viral proteins have a variety of functions. The matrix (M) protein of the respiratory pathogen human metapneumovirus (hMPV) contains two such conserved motifs-YSKL and YAGL.We mutated these sequences to analyze their contributions to hMPV infectivity. The mutant clones were capable of intracellular replication; however, the YAGL but not YSKL mutants were defective at spreading in infected cultures. We improved the reverse genetics system for hMPV and generated cell lines that stably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 90 publications
0
31
0
Order By: Relevance
“…Second, there may be other unknown ESCRT components, pathways, or viral protein substitutes that can function redundantly in certain circumstances and, thus, may compensate when the canonical late-domain sequences are disrupted or the activity of Vps4 is inhibited. This may explain the requirement for late-domain sequences in the budding of a collection of viruses that are insensitive to Vps4 inhibition, including Ebola virus, metapneumovirus (MPV), Newcastle disease virus, Sendai virus, and vesicular stomatitis virus (VSV) (Gosselin-Grenet et al 2007, Irie et al 2004, Neumann et al 2005, Sabo et al 2011, Schmitt et al 2005, Shnyrova et al 2007). Finally, these viruses may use another method of membrane scission in addition to the host ESCRT system, providing a measure of redundancy in the event that one of the scission pathways malfunctions (Figure 4).…”
Section: Viral Mechanisms Of Membrane Scissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there may be other unknown ESCRT components, pathways, or viral protein substitutes that can function redundantly in certain circumstances and, thus, may compensate when the canonical late-domain sequences are disrupted or the activity of Vps4 is inhibited. This may explain the requirement for late-domain sequences in the budding of a collection of viruses that are insensitive to Vps4 inhibition, including Ebola virus, metapneumovirus (MPV), Newcastle disease virus, Sendai virus, and vesicular stomatitis virus (VSV) (Gosselin-Grenet et al 2007, Irie et al 2004, Neumann et al 2005, Sabo et al 2011, Schmitt et al 2005, Shnyrova et al 2007). Finally, these viruses may use another method of membrane scission in addition to the host ESCRT system, providing a measure of redundancy in the event that one of the scission pathways malfunctions (Figure 4).…”
Section: Viral Mechanisms Of Membrane Scissionmentioning
confidence: 99%
“…However, a capacity to alter membrane curvature has not yet been demonstrated for Rab11-FIP2, and thus the mechanism of action remains unknown. Interestingly, budding of the closely related avian and human MPV is also ESCRT independent (Sabo et al 2011, Weng et al 2011), though no dependence on Rab11-FIP2 has yet been found for MPV.…”
Section: Viral Mechanisms Of Membrane Scissionmentioning
confidence: 99%
“…The HA-tagged proteins were detected using a primary monoclonal antibody directed against HA (Roche) and a secondary goat anti-mouse antibody conjugated with fluorescein isothiocyanate (FITC). HMPV M protein was detected using an antibody against the avian metapneumovirus C M protein, kindly provided by Sagar M. Goyal (University of Minnesota, Minneapolis, MN), which has been shown to cross-react with HMPV M (40), and a secondary goat anti-rabbit antibody conjugated with TRITC. Pictures were taken using the Nikon 1A confocal microscope and analyzed with the NIS-Elements software.…”
Section: Methodsmentioning
confidence: 99%
“…MPV encodes 9 proteins: nucleocapsid (N), phosphoprotein (P), matrix (M), fusion (F), M2 with two open reading frames (M2-1, M2-2), small hydrophobic (SH), glycoprotein (G), and polymerase (L). Most of the HMPV proteins are analogous to other paramyxovirus proteins, with analogous functions (Cai et al, 2015; de Graaf et al, 2008; Derdowski et al, 2008; Kitagawa et al, 2010; Leyrat et al, 2014a; Leyrat et al, 2013; Leyrat et al, 2014b; Miller et al, 2007; Sabo et al, 2011; van den Hoogen et al, 2002). …”
Section: Introductionmentioning
confidence: 99%